Restructuring Korea Inc - Shin, Jang-Sup, 1962- (RoutledgeCurzon studies in the growth economies of Asia, 2003)
"Looking first at the strengths and weaknesses of 'Korea Inc.' in comparison with other East Asian countries, the authors describe the challenges faced by Korea in the 1990s due to the acceleration of globalisation. By arguing that the transition attempted by Korea was badly conceived and ill designed, Restructuring Korea Inc. focuses on corporate reform after the crisis that has led to the running up of huge 'transition costs'."